Change of salt tolerance in common wheat after introgression of genetic material from Aegilops speltoides and Triticum timopheevii - R. S. Yudina; I. N. Leonova; E. A. Salina; E. K. Khlestkina (Вавиловский журнал генетики и селекции, 2015)
To improve biotic and abiotic stress tolerance in common wheat (Triticum aestivum L.), novel genotypes with genomic fragments introgressed from other cereal species are extensively developed. One of the most important abiotic environmental factors that impede the expansion of wheat cultivation areas is soil salinity. Salt-sensitive wheat varieties have poor yield and impaired grain quality when exposed to salinity. The aim of this study was to evaluate the degree of influence of alien genetic material on salinity tolerance in common wheat seedlings. Seedlings of introgression lines carrying single fragments of Aegilops speltoides and T. timopheevii genomes in common wheat chromosomes 2А, 5В, and 6В, were tested for salt tolerance. The parental common spring wheat genotypes Saratovskaya 29, Novosibirskaya 29 and Rodina-1, possessing mode- rate salt tolerance, were used as reference. The expe- riment showed that the presence of the translocation T5BS • 5BL-5SL either in Novosibirskaya 29 or in Rodina-1 increased salt tolerance. On the contrary, another translocation between T. aestivum and Ae. speltoides (T6BS • 6BL-6SL) made wheat more sensitive to salinity. Different fragments of T. timo- pheevii genome had different effects: introgression into the chromosome 2A increased salt tolerance, whereas introgression into chromosome 5B reduced it significantly. The observed differences between the parental wheat genotypes and the introgression lines derived from them are discussed with regard to the locations of alien introgression fragments in the lines tested and the map positions of known wheat QTLs and major genes related to salt tolerance. It is assumed that a locus yet undescribed that affects wheat salt tolerance is located distal to the Xgwm0604 marker on the long arm of chromosome 5B.